NEOADJUVANT RADIATION THERAPY FOR RECTAL CANCER WITH SYNCHRONOUS LIVER METASTASES (LITERATURE REVIEW) - T. P. Pochuev; A. A. Nevolskikh; L. O. Petrov; L. N. Titova; A. A. Karpov (Сибирский онкологический журнал, 2021)
Background. In Russia, synchronous distant metastases are annually detected in approximately 6,200 patients and synchronous liver metastases in 4,000 patients. To plan treatment for rectal cancer with synchronous liver metastases, it is necessary to consider the location of the tumor, extent of the primary tumor involvement, tumor-related complications, and resectability of metastases.The purpose of this review was to analyze the results of studies aimed at finding the best regimens for treating rectal cancer patients with synchronous liver metastases.Material and Methods. The review includes both retrospective and prospective studies devoted to treatment of rectal cancer with synchronous liver metastases. Previous reviews and clinical recommendations were analyzed.Results. Most oncologists are in favor of preoperative radiotherapy, especially when rectal cancer is located in the lower-and middle-ampullary regions. However, there are no randomized trials with a representative number of patients to confirm or refute this point of view. Due to the increased life expectancy of patients and introduction of modern minimally invasive surgical approaches, there is an urgent need for radical treatment of rectal cancer patients. Thus, the approaches to the treatment of primary tumors with synchronous metastatic liver damage should be the same as in stage II–III of the disease, and neoadjuvant radiation therapy is an integral part of this strategy.